2020
DOI: 10.1142/s0219455420500923
|View full text |Cite
|
Sign up to set email alerts
|

Displacement Transmissibility of a Four-Parameter Isolator with Geometric Nonlinearity

Abstract: This study is concerned with structural vibration reduction using a four-parameter isolator designed as a scissor-like structure, which can induce geometric nonlinearity during the deformation process. The displacement transmissibility of the isolator including the geometric nonlinearity under base excitations is thoroughly investigated. First, the dynamic model of the four-parameter isolator is presented. Then, by utilizing the harmonic balanced method (HBM), the steady-state solutions of the inertia mass and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…After the previous discussion, it is confirmed that the fourparameter-VI exhibits improved comprehensive vibration isolation performance over a wide frequency band. The fourparameter system can be realized in various ways, such as flow channels [21], scissor-like structures [22], smart spring [23,24], etc. The giant electrorheological (GER) fluid is a kind of smart materials whose mechanical properties can be adjusted by an external electric field.…”
Section: Structural Configuration and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the previous discussion, it is confirmed that the fourparameter-VI exhibits improved comprehensive vibration isolation performance over a wide frequency band. The fourparameter system can be realized in various ways, such as flow channels [21], scissor-like structures [22], smart spring [23,24], etc. The giant electrorheological (GER) fluid is a kind of smart materials whose mechanical properties can be adjusted by an external electric field.…”
Section: Structural Configuration and Discussionmentioning
confidence: 99%
“…Shi et al [21] proposed a novel passive isolator based on the four-parameter Zener model and derived the equivalent stiffness and damping model of the isolator from the dynamic stiffness of the isolation system. Liu et al [22] studied a four parameter isolator designed as a scissorlike structure, which can induce geometric nonlinearity during the deformation process. Ni et al [23,24] studied the vibration transmissibility characteristics of the smart spring systems with a four-parameter equivalent model, and discussed the influences of system parameters on the vibration transmissibility characteristics.…”
Section: Introductionmentioning
confidence: 99%